Experiences of mothers with preterm babies at a Mother and Baby Unit of a tertiary hospital: A descriptive phenomenological study - Alberta Yemotsoo Lomotey; Victoria Bam; Abigail Kusi‐Amponsah Diji; Ernest Asante; Hannah Boatemaa Asante; Joyce Osei (Wiley, 2020)
Abstract Aim To describe the lived experiences of mothers with preterm babies at a Mother and Baby Unit (MBU) of a tertiary hospital. Design A descriptive phenomenological approach. Method Ten mothers were purposively sampled during the month of May, 2017 to describe their experiences of having preterm babies. Recorded in‐depth individual interviews were transcribed verbatim; codes were generated and inductively organised into themes. Results Four themes were actively generated: 'Emotional experiences of mothers', 'Mother‐baby interaction', 'Perception on care and support' and 'Challenges within Mother and Baby Unit environment'. Mothers were anxious about the premature delivery and were afraid of possible infant's death. They cherished interactions with their babies during kangaroo mother care and breastfeeding. Mothers applauded the nurses for their professional competence. They expressed concerns about inadequate accommodation, high cost of care, the frequency and duration of mother-baby interactions.